2009
DOI: 10.1001/archgenpsychiatry.2008.539
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychiatric and Substance Use Disorders Among Single Mothers Nearing Lifetime Welfare Eligibility Limits

Abstract: Despite the high prevalence of psychiatric and substance use disorders in this population, many remain untreated. The consequences of terminating welfare assistance are worthy of further investigation, given the potential for adverse effects on both mothers and their young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
(36 reference statements)
3
18
2
Order By: Relevance
“…Uninsured TANF leavers who report poor mental health are relatively unlikely to seek treatment (28). Conversely, a woman whose income qualifies her for TANF becomes relatively likely to get care as needed (19,29). TANF enrollment, then, seems to promote use of mental health and substance abuse services.…”
Section: Enabling Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Uninsured TANF leavers who report poor mental health are relatively unlikely to seek treatment (28). Conversely, a woman whose income qualifies her for TANF becomes relatively likely to get care as needed (19,29). TANF enrollment, then, seems to promote use of mental health and substance abuse services.…”
Section: Enabling Factorsmentioning
confidence: 99%
“…Studies show African-Americans commonly cite fear and mistrust of such providers as a reason for avoiding mental health treatment (21). One study of TANF recipients' ethnicity (together with their education and marital status), however, showed that ethnicity (and education and marriage alike) made no significant impact on treatment seeking for mental disorders or addiction; only the recipients' advancing age was found to be associated with the decision to pursue treatment (19).…”
Section: Predisposing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates suggest that between one fourth and one third of women on welfare experience some combination of post-traumatic stress disorder (PTSD), depression, generalized anxiety disorder (GAD), or substance abuse/misuse. 28 More recently, Cook et al (2009) found that among single mothers on welfare, 61% of mothers reported a lifetime rate of any DSM-IV disorder; 46.8% of mothers reported at least one disorder in the past 12 months. 29 The lifetime and 12-month rates for specific disorders were substance use disorder (SUD;29.1%, 9%), mood disorders (28.8%, 20.1%), and anxiety disorders (47.1%, 39.0%).…”
Section: Psychological Needs Of Low-income Women Are Still Unmetmentioning
confidence: 99%
“…Substance-dependent parenting women are a complex population with problems in multiple areas including education, employment, housing, mental and physical health, and legal issues (Cook et al, 2009). Children of these women are at high risk of poor developmental, behavioral, and emotional outcomes, as well as increased involvement in the child welfare system (Barnard & McKeganey, 2004).…”
Section: Introductionmentioning
confidence: 99%